EXECUTION OF FINAL AND BINDING COURT DECISIONS IN CORRUPTION CRIMES BY PROSECUTORS (A CASE STUDY OF THE SERDANG BEDAGAI DISTRICT PROSECUTOR'S OFFICE) - Dinda Sundari; Triono Eddy; Juli Moertiono (Journal Analytica Islamica, 2025)
The execution of court decisions in corruption cases falls under the authority of prosecutors as regulated in Article 270 of the Indonesian Criminal Procedure Code (KUHAP). Prosecutors act both as public prosecutors and as executors of court rulings that have obtained permanent legal force. This study aims to analyze the authority of prosecutors in executing corruption cases, to identify the challenges encountered, and to formulate effective countermeasures. The research employs an empirical juridical method with a qualitative approach, combining normative analysis and field data to achieve a comprehensive understanding. The findings indicate that prosecutors play a central role in the execution process, including the enforcement of additional criminal sanctions. However, execution is often hindered by regulatory disharmony, the absence of standardized SOPs, limited inter-agency coordination, as well as social and political pressures. Therefore, strengthening prosecutorial professionalism, establishing clear SOPs, enhancing cross-institutional coordination, providing legal protection for prosecutors, and fostering public involvement in oversight are necessary. These efforts are expected to improve the effectiveness of execution, ensure legal certainty, and enhance public trust in the judicial system for corruption cases.